Structural tuning of heterogeneous molecular catalysts for electrochemical energy conversion - Wang, Jiong (2021)
Heterogeneous molecular catalysts based on transition metal complexes have received increasing attention for their potential application in electrochemical energy conversion. The structural tuning of first and second coordination spheres of complexes provides versatile strategies for optimizing the activities of heterogeneous molecular catalysts and appropriate model systems for investigating the mechanism of structural variations on the activity. In this review, we first discuss the variation of first spheres by tuning ligated atoms; afterward, the structural tuning of second spheres by appending adjacent metal centers, pendant groups, electron withdrawing/donating, and conjugating moieties on the ligands is elaborated. Overall, these structural tuning resulted in different impacts on the geometric and electronic configurations of complexes, and the improved activity is achieved through tuning the stability of chemisorbed reactants and the redox behaviors of immobilized complexes.